OPTIMALISASI PEMANFAATAN LAHAN PEKARANGAN RUMAH DI NAGARI KOTO BARU KECAMATAN LUHAK NAN DUO KABUPATEN PASAMAN BARAT - Rahmah, Softi Nur; Edial, Helfia; Yuherman, Yuherman (STKIP PGRI Sumbar, 2013)
This research aimed to obtain information, analyze and discuss data on the optimization the utilization of homestead land in Luhak Nan Duo District Nagari Koto Baru West Pasaman Regency. Type of research was descriptive correlational. The research population was a whole head of the family/ homemakers who has a homestead in Luhak Nan Duo District Nagari Koto Baru West Pasaman Regency. Samples from this research area is a residential region in Nagari Koto Baru by taken three were deemed to represent the ellipse is Jorong Sei. Talang, Jorong Jambak, and Jorong Ophir. Respondent sampling done by used proportional random sampling technigue by taken a sample of 80 respondents and data collection through questionnaire distribution. Based on a simple linear regression analysis, double (multiple) and the correlation it can be concluded as follows: (1) Found the influence of education on the level of optimization the utilization of homestead land in Nan Duo District Nagari Koto Baru West Pasaman Regency because t count > t table ( 6.936 > 2.00), power relations were high (r = 0.618) and the contributions gave 38.1%, (2) Found the spacious homestead land influence toward optimization the utilization of homestead land in Luhak Nan Duo District Nagari Koto Baru West Pasaman Regency because t count > t table (6.809 > 2.00), power relations were high (r = 0.611) and the contributions gave 37.3%, (3) Found the influence of free time toward optimization the utilization of homestead land in Luhak Nan Duo District Nagari Koto Baru West Pasaman Regency because t count > t table (4.685 > 2.00), the strength of the relationship enough category (r = 0.469) and the contributions gave 22% and (4) Found the influence of the level of public education, spacious homestead and free time together toward optimize the utilization of homestead land in Luhak Nan Duo District Nagari Koto Baru West Pasaman Regency because F count > F table (42.778 > 3.96), the strength of the relationship between three variables toward optimize the utilization of homestead in Luhak Nan Duo District Nagari Koto Baru West Pasaman Regency included were high (r = 0.793) and higher contributions gave 62.8%.